Consultations and antibiotic treatment for urinary tract infections in Norwegian primary care 2006–2015, a registry-based study - Haugom, Lars Emil Aga (BMC Fam Pract, 2021)
BACKGROUND: Extensive use of antibiotics and the resulting emergence of antimicrobial resistance is a major health concern globally. In Norway, 82% of antibiotics is prescribed in primary care and one in four prescriptions are issued for the treatment of urinary tract infections (UTI). The aim of this study was to investigate time trends in antibiotic treatment following a consultation for UTI in primary care. METHODS: For the period 2006–2015 we linked data from the Norwegian Registry for Control and Payment of Health Reimbursements on all patient consultations for cystitis and pyelonephritis in general practice and out-of-hours (OOH) services, and data from the Norwegian Prescription Database on all dispensed prescriptions of antibiotics. RESULTS: Altogether 2,426,643 consultations by attendance for UTI took place in the study period, of these 94.5% for cystitis and 5.5% for pyelonephritis. Of all UTI consultations, 79.4% were conducted in general practice and 20.6% in OOH services. From 2006 to 2015, annual numbers of cystitis and pyelonephritis consultations increased by 33.9 and 14.0%, respectively. The proportion of UTI consultations resulting in an antibiotic prescription increased from 36.6 to 65.7% for cystitis, and from 35.3 to 50.7% for pyelonephritis. These observed changes occurred gradually over the years. Cystitis was mainly treated with pivmecillinam (53.9%), followed by trimethoprim (20.8%). For pyelonephritis, pivmecillinam was most frequently used (43.0%), followed by ciprofloxacin (20.5%) and sulfamethoxazole-trimethoprim (16.3%). For cystitis, the use of pivmecillinam increased the most during the study period (from 46.1 to 56.6%), and for pyelonephritis, the use of sulfamethoxazole-trimethoprim (from 11.4 to 25.5%) followed by ciprofloxacin (from 18.2 to 23.1%). CONCLUSIONS: During the 10-year study period there was a considerable increase in the proportion of UTI consultations resulting in antibiotic treatment. Cystitis was most often treated with pivmecillinam, and this proportion increased during the study period. Treatment of pyelonephritis was characterized by more use of broader-spectrum antibiotics, use of both sulfamethoxazole-trimethoprim and ciprofloxacin increased during the study period. These trends, indicative of enduring changes in consultation and treatment patterns for UTIs, will have implications for future antibiotic stewardship measures and policy.